5m+2m=3m+4

Simple and best practice solution for 5m+2m=3m+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5m+2m=3m+4 equation:


Simplifying
5m + 2m = 3m + 4

Combine like terms: 5m + 2m = 7m
7m = 3m + 4

Reorder the terms:
7m = 4 + 3m

Solving
7m = 4 + 3m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-3m' to each side of the equation.
7m + -3m = 4 + 3m + -3m

Combine like terms: 7m + -3m = 4m
4m = 4 + 3m + -3m

Combine like terms: 3m + -3m = 0
4m = 4 + 0
4m = 4

Divide each side by '4'.
m = 1

Simplifying
m = 1

See similar equations:

| 7x^4(-x^3+9x^2-9x+1)= | | F=1.8*-11+32 | | (x-4)-(3x-1)=4 | | x^2+10-21=(x+3)(x-7) | | X(3x)=8(6) | | h(t)=-16t^2+106t+329 | | 24+6m=24-6m | | 4.3x+4.7=17.6 | | 4+2x+5-x=27 | | 2(x-1)+10=4+3(6x-5) | | 5k(-4)/2=5 | | -1/10(20) | | 2(x+x)=162 | | .4x+.03x=7.30 | | 7/h=8/9 | | 25-9x+4+2x=0 | | 10x-89=100 | | 8(y-7)=-8y+8 | | -16=-7r+5 | | 2(u+4)=-6(3u-3)+2u | | 3+5w=54 | | X/9=-10/13 | | 4.4(3+4x)-1.2=12 | | 1/2-6.512= | | 8d-d-2d+5=2d | | 5t+12-4t=0 | | 4.7d+4.1=-2.3+0.53 | | 3a-9=-63 | | -5x+12=2(x+1) | | .20(10)+x=.50(x+10) | | 2/16=8/ | | x+6=(2x-3) |

Equations solver categories